1998
DOI: 10.1046/j.1365-3083.1998.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Concanavalin A‐Induced Murine Liver Injury by the Organic Germanium Compound, Propagermanium

Abstract: Propagermanium (3-oxygermylpropionic acid polymer) is an organic germanium compound that activates the immune system. In this study, we investigated the action of propagermanium on T-cell-mediated murine hepatic injury induced by concanavalin A (Con A). Oral administration of propagermanium inhibited the development of liver injury about 10 h after ConA injection. Histological analysis demonstrated that propagermanium attenuated the extent of liver damage compared with controls, reducing infiltration by leucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…This concentration of propagermanium in the feeding chow results in an approximate dose of 5 mg/kg and 50 mg/kg body weight per day in each mouse, respectively, adjusted for previous measurement of food intake. This dose had no significant effect on normal mice 20) and caused no deaths in this study. The IC50 value for propagermanium inhibition of CCR2 is 0.52 g/mL 21) .…”
Section: Animal Preparation and Experimental Designmentioning
confidence: 58%
See 1 more Smart Citation
“…This concentration of propagermanium in the feeding chow results in an approximate dose of 5 mg/kg and 50 mg/kg body weight per day in each mouse, respectively, adjusted for previous measurement of food intake. This dose had no significant effect on normal mice 20) and caused no deaths in this study. The IC50 value for propagermanium inhibition of CCR2 is 0.52 g/mL 21) .…”
Section: Animal Preparation and Experimental Designmentioning
confidence: 58%
“…The molecular mechanism of the action of propagermanium has been explained by its targeting glycosylphosphatidylinositol-anchored proteins that are closely associated with CCR2 and the resulting blockade of MCP-1/CCR2-mediated signaling 21) . Many animal studies have shown that propagermanium improves liver injury 20,23) , atherosclerosis 24) and diabetic nephropathy 25,26) by reducing monocyte/macrophage infiltration into the lesion. In this study we demonstrated that inhibition of CCR2 C D function by propagermanium treatment reduced macrophage infiltration into adipose tissue in DIO mice as well as db/db mice 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous reports help us understand our results. Ishiwata et al 56 showed that mice treated with propagermanium (the organic germanium compound) were resistant to ConA-induced hepatitis, while CD4 + T-cell liver infiltration remained unchanged. Recently, Wolf et al 57 indicated that TNFR1 À/À and TNFR2 À/À mice were resistant to ConA-induced hepatitis, while infiltration of CD4 + T cells in liver also remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ge-132, has a strong activity on inducing the generation of exogenous IFN in chickens [116] [126] [127]. The propagermanium can improve hepatitis through reducing the gereration of TNF-α [128]. The levels of IFN-γ, IL-1α, IL-1β, and IL-4 gene expression were also significantly increased after treated with germanium biotite [118].…”
Section: Effects Of Germanium On Cytokinesmentioning
confidence: 99%